Application of PDCA cycle in continuous quality improvement of elective surgery schedule (运用PDCA循环持续改进首台择期手术开台时间管理质量) - SUN Yifan (孙铱钒); XU Xu (徐旭); WANG Yuena (王岳娜) (中西医结合护理)
Objective To evaluate the effect of PDCA cycle in continuous quality improvement of elective surgery schedule. Methods The first case on-time starts of the day between July 2020 and July 2021 was retrospectively analyzed. The PDCA cycle was used to in the management of first case on-time starts of the day. The difference in first case on-time starts before and after implementation of PDCA cycle was analyzed. Results The rate of first case on-time starts was increased after implementation of PDCA cycle, and potential risks causing the delay of first case on-time starts were addressed. Conclusion The implementation of PDCA cycle is effective to increase the awareness of first case on-time starts among surgeons, anesthesiologist, surgical nurses and other medical workers. The PDCA cycle helps hospital managers to establish scientific process and improve the management quality of elective surgery schedule. (目的 探讨运用PDCA循环持续改进首台择期手术开台时间管理质量的效果。方法 调查和分析医院2020年7月—2021年7月首台择期手术开台时间, 应用PDCA循环进行首台择期手术开台时间管理, 对比分析实施PDCA管理前后手术开台时间。结果 实施PDCA循环后, 医院首台择期手术开台时间较实施PDCA循环前提前, 首台择期手术开台时间延迟的问题得到改善。结论 PDCA循环的实施提高了医院外科科室、手术麻醉科等对首台择期手术准时开台的重视程度, 相关制度要求逐项落实, 首台择期手术开台时间管理质量得到提升。)